Gambaran Kesejahteraan Psikologis Mahasiswa Program Profesi Ners Selama Menjalani Praktik Klinik di Masa Adaptasi Kebiasaan Baru - Dyah Setyorini; Hanna Aulia Zahra; Indra Maulana; Henny Yulianita; Iyus Yosep (Universitas Malahayati Lampung, 2024)
ABSTRACT To maintain people's productivity during the COVID-19 pandemic, the Indonesian government has issued a new policy where people can remain productive with the Adaptation to New Habits (IMR) system. One of the sectors affected by the AKB system is the world of education which has been shifted from an online system to face-to-face learning. This change has quite an impact on students, especially nursing students, who find it quite difficult to deal with clinical practice, so they often experience mental tension and experience a decline in psychological well-being. This study aims to obtain an overview of student's psychological well-being in the Nursing Professional Program (PPN) while undergoing clinical practice during the AKB period. This research uses a quantitative descriptive design. The research subjects were students of the Nursing Professional Program (PPN) class 44, Faculty of Nursing, Padjadjaran University using a total sampling technique (N=93). Data collection was carried out using the Indonesian version of the Psychological Well-Being Scale (PWBS) instrument which is valid and reliable from Rachmayani Ramdhani (2014) with a validity test value of 0.304 to 0.508 and a reliability test value of 0.921. Research shows that most respondents (96%) have low psychological well-being scores. This is influenced by changes in learning methods, the pandemic situation, and various academic challenges that cause various psychological problems in students during clinical practice. The level of psychological well-being of PPN 44 students during clinical practice is mostly in the low category. Therefore, researchers suggest providing counseling services for students to reduce the psychological pressure they experience so that their psychological well-being can improve. Keywords: Adaptation to New Habits, Clinical Practice, Psychological Well-Being, Students ABSTRAK Dalam rangka menjaga produktivitas masyarakat di tengah pandemi COVID-19, pemerintah Indonesia mengeluarkan kebijakan baru dimana masyarakat bisa tetap produktif dengan sistem Adaptasi Kebiasaan Baru (AKB). Salah satu sektor yang terdapak dengan sistem AKB adalah dunia pendidikan yang dialihkan dari sistem daring menjadi pembelajaran tatap muka. Perubahan ini cukup berdampak pada mahasiswa terutama mahasiswa keperawatan yang merasa cukup kesulitan dalam menghadapi praktik klinik sehingga sering mengalami ketegangan mental dan mengalami penurunan kesejahteraan psikologis. Penelitian ini bertujuan untuk mendapatkan gambaran mengenai kesejahteraan psikologis pada mahasiswa Program Profesi Ners (PPN) selama menjalani praktik klinik di masa AKB. Penelitian ini menggunakan desain desktriptif kuantitatif. Subjek penelitian pada mahasiswa Program Profesi Ners (PPN) angkatan 44 Fakultas Keperawatan Universitas Padjadjaran dengan teknik total sampling (N=93). Pengumpulan data dilakukan dengan menggunakan instrumen Psychological Well-Being Scale (PWBS) versi Bahasa Indonesia yang sudah valid dan reliabel dari Rachmayani Ramdhani (2014) dengan nilai uji validitas sebesar 0,304 sampai 0,508 dan nilai uji reliabilitas sebesar 0,921. Penelitian menunjukkan bahwa sebagian besar responden (96%) memiliki skor kesejahteraan psikologis yang rendah. Hal ini dipengaruhi oleh perubahan metode pembelajaran, situasi pandemi, dan berbagai tantangan akademik yang menyebabkan berbagai permasalahan psikologis pada mahasiswa selama melaksanakan praktik klinik. Tingkat kesejahteraan psikologis mahasiswa PPN 44 selama menjalani praktik klinik sebagian besar berada pada kategori rendah. Oleh karena itu, peneliti menyarankan agar menyediakan layanan konseling bagi mahasiswa untuk mengurangi tekanan psikologis yang dialami sehingga kondisi kesejahteraan psikologis dapat meningkat. Kata Kunci: Adaptasi Kebiasaan Baru, Kesejahteraan Psikologis, Mahasiswa, Praktik Klinik